DIALOG ANTARGENERASI: STRATEGI MISIOLOGI DALAM MENJANGKAU GENERASI Z DAN ALPHA - Dapot Damanik; Saktina M. Manullang; Mega Melati Munte; Royda Togatorop; Edward Coco Priyono Pardede (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This article discusses the importance of intergenerational dialogue as a missiological strategy for reaching Generation Z and Alpha in the digital era. Cultural, technological, and cognitive shifts require the church and Christian educational institutions to move away from rigid and one-way approaches. Generation Z and Alpha are characterized by their strong connection to technology, critical thinking patterns, and more personal and contextual spirituality. This condition calls for a dialogical, inclusive, and relational approach to faith education. Through a multidisciplinary review, this article emphasizes the need to transform learning methods from absolute to dialogical and participatory. The intergenerational approach is seen as essential in building faith through relationships, mutual learning, and authentic value transmission. In addition, the role of family, church, school, and the digital environment is crucial in shaping the spiritual development of young generations. The article proposes practical strategies such as curriculum renewal based on dialogue, utilization of digital technology, empowering leadership, and intergenerational worship practices. With this holistic approach, the church is expected to be more effective in nurturing Generation Z and Alpha to become faithful, relevant, and ready to face contemporary challenges